2016
DOI: 10.1161/circulationaha.115.020950
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dabigatran and Warfarin in Patients With Atrial Fibrillation and Valvular Heart Disease

Abstract: URL: http://www.clinicaltrials.gov. Unique identifier: NCT00262600.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(70 citation statements)
references
References 13 publications
5
60
0
5
Order By: Relevance
“…Previous post hoc analyses of patients with VHD included in the pivotal NOAC trials showed increased stroke and major bleeding risk among patients with VHD, similar to our study findings 8, 9, 10. The relative benefits of NOACs were comparable in patients with and without VHD, despite higher thromboembolic and bleeding risk in the VHD cohorts.…”
Section: Discussionsupporting
confidence: 90%
“…Previous post hoc analyses of patients with VHD included in the pivotal NOAC trials showed increased stroke and major bleeding risk among patients with VHD, similar to our study findings 8, 9, 10. The relative benefits of NOACs were comparable in patients with and without VHD, despite higher thromboembolic and bleeding risk in the VHD cohorts.…”
Section: Discussionsupporting
confidence: 90%
“…However, we used a broader definition in this study because the severity of valvular disease was not well documented in the EMRs, and we were collecting data from as far back as 2010, when older definitions of valvular AF were in place. Moreover, in light of emerging evidence that patients with nonprosthetic valvular AF may still derive benefits from these agents,10 we felt that DOACs may not necessarily be inappropriate in these cases. The second caveat with our findings is that we did not classify a DOAC prescription for the 9% of patients with CHADS scores of 0 as inappropriate, although some guidelines would,11, 12 because we did not know if those patients had cardioversions planned, and we were not privy to the discussions between clinicians and patients about their values and preferences with respect to stroke prevention versus bleeding risk.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies found that efficacy of rivaroxaban or apixaban or dabigatran versus warfarin was similar in patients with atrial fibrillation and other types of valvular heart disease. [2,28,29] In the present report, rivaroxaban can even dissolve the LAA thrombi in patients with severe mitral stenosis, indicating that this drug could be a therapeutic option for patients with mitral stenosis. However, before its use can be recommended in patients with rheumatic mitral stenosis, additional randomized data are needed to prove these preliminary findings.…”
Section: Discussionmentioning
confidence: 50%